Effects of transitional care based on the social support theory for older patients with osteoporotic vertebral compression fractures: A quasi‐experimental trial. (22nd August 2022) - Yang, Wenwen; Xu, Haiyan; Miao, Weiwei; Geng, Zihan; Geng, Guiling
Abstract: Objectives: This study aimed to investigate the effects of transitional care (TC) programs on the health outcomes of discharged older patients with osteoporotic vertebral compression fractures (OVCFs). Methods: A total of 160 older patients were recruited from two campuses of a public teaching hospital in China. Patients were grouped according to the campus to which they were admitted. The TC programs commenced one day before discharge and lasted 6 months after discharge. Repeated‐measures analysis of variance was used to analyse the effects of the TC programs. Results: The TC programs improved the discharge of older patients with OVCF in their activities of daily living (ADLs), pain levels and social support, and decreased fracture recurrence rates. Conclusions: This study provides evidence of concurrent clinical improvements and health outcomes in discharged older patients with OVCFs from the effects of TC programs based on social support theory.